(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article deals with the problem of the multivariance of the names of biblical characters in fiction and journalistic texts in the Belarusian language (such as: Jesus Christ, Abraham, Daniel, Zechariah, etc.). Further, this article discusses the specifics and variations of the usage of biblical proper names, taken from the Old Testament. The contexts are taken from the works of Belarusian writers, as well as fiction and journalistic texts translated into Belarusian language. Based on the specificity of the use of biblical proper names, the names were divided into 5 groups: 1) the bibleism is used as a character in a work based on biblical myths; 2) the bibleism is used in a reference to the biblical text; 3) the bibleism is used in metaphors / comparisons; 4) the bibleism is used as a part of a phraseological unit, 5) the bibleism is used in a direct quotations from the Bible. Further, as a result of the analysis, we found out that although the use of biblical proper names is similar in fiction and journalistic texts, there are still differences. Due to the small number of examples, we can conclude that the biblical names that came into use from the Old Testament are not widespread in journalistic texts in the Belarusian language, and are used mainly in the form of quotes, metaphors and comparisons as arguments to confirm their point of view. Biblical proper names that are parts of the metaphors, comparisons and phraseological units are common for literary texts. In addition, a certain variety of spelling of biblical names in the Belarusian language necessitates their standardization for adequate perception and identification in the speech of native speakers.